(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
The historic Sri Sri Ganesh Temple at Lalmati-Duramari of Abhayapuri located in the district of Bongaigaon, Assam stands as a strong symbol of the deep bond between cultural heritage and religious devotion. Although its exact origin is lost in the flow of oral stories, the temple has grown over many generations into an important cultural centre for the communities of the region. This paper looks at the temple through a literary and historical approach, placing it within the wider traditions of Assamese spirituality, social identity, and shared memory. Using oral accounts, observations, and cultural study, the research shows that the temple is not only a place of worship but also a living record of many layers of cultural history. It explores the living architecture of the temple, its rituals, natural surroundings and its importance in passing heritage from one generation to the next. The study concludes that the Sri Sri Ganesh Temple is embellished with tradition and culture, keeping the ancient spiritual practices alive, while remaining closely connected to modern life in Abhayapuri.